Comparison of Online Assessment with Traditional Assessment of Ophthalmology Students: Experience from Public Sector Medical College in Pakistan: Doi: 10.36351/pjo.v37i4.1330 - Ayub, Muhammad Hammad; Ali, Muhammad Hassaan; Hamza, Uzma; Jahangir, Kashif (Pakistan Journal of Ophthalmology, 2021)
Purpose: To perform online assessment of undergraduate ophthalmology students and compare the online examination results with conventional in-person examination during COVID-19 pandemic. Study Design: Comparative, cross-sectional study. Place and Duration of Study: Department of Ophthalmology, Allama Iqbal Medical College, Lahore, Pakistan. From October 2019 to December 2020. Methods: We used online Google Assessment Forms to administer the online ophthalmology send-up examination to 4th-year MBBS students. The exam consisted of 50 test items with varying difficulty levels and pictures were incorporated into them. The examination results were compared with the conventional face-to-face send-up ophthalmology examination conducted a year ago, which consisted of 50 multiple-choice questions (MCQs). Results: There were 50 questions in the online examination with categorization into C1:C2:C3 levels of cognition. A total of 336 students submitted their responses for online assessment with a mean score of 36.28 out of 50 marks (73.0%) (Range: 7 – 45 marks). C1, C2, and C3 questions were correctly answered by 95.3%, 45.1%, and 11.0% of the students, respectively. The conventional examination was taken by 326 students and consisted of 50 MCQs with C1:C2:C3 questions. The online exam yielded more mean scores than the in-person exam (73.0% versus 56.0%, p-value: 0.001). The rate of failure with scores less than 50% marks was significantly higher in students appearing in conventional exam versus online exam (16.6% versus 1.5% respectively, p-value: 0.0412). Conclusion: Online assessment of undergraduate ophthalmology students is a possible alternative to the conventional examinations during this pandemic. Key Words: Ophthalmology, COVID-19 Pandemic. Medical education.